Evaluation of the Efficacy of Local Isolates 28 Bacteria Bacillus thuringiensis with Standard Isolation B.t. Kurstaki on Ephestia cautella with the Genetic Classification of Selected Isolates (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The study included 28 local isolates with standard isolation B.t.kurstaki. The statistical analysis of the results of bio-evaluation on the Ephestia cautella larvae showed that the standard isolation B.t.kurstaki gave very high killing results of 100% at the first concentration of 1.2 × 106 spor / g after ten days of treatment superior to All isolates were followed by isolation of IN-1, which resulted       in a 90% kill with a concentration of 1.2 × 106 spor / g followed by isolation of NJ-1, killing 73.3% at a concentration of 1.2 × 106 spor / g. Cry1 was found in the standard isolation B.t.kurstaki and the local isolation NJ-1, where the size of the gene was 260-280bp. The isolation of the NJ-1 was found to be serovar B.t.kurstaki. When we used the Cry9 gene, we obtained this gene in local isolation, IN-1, and we did not obtain this gene in the other isolates, as the size of the gene was 345-360 bp, and it was shown that the isolation was serovar B.t.aizawai.